Enhancing Musical Literacy in University Choirs Using Kodály Hand Signs and Culturally Adapted Syllables - Masni Fanshuri; Ardipal Ardipal; Paul H Mason; Masni Erika (AT-TA'LIM, 2026)
This study evaluates the effectiveness of the Kodály Method specifically hand sign and rhythm syllable techniques in improving the musical literacy of non-music major university students. Addressing the prevalent issue of passive imitation in student choirs, this research employed a quantitative quasi-experimental post-test only control group design involving 40 participants from the Universitas Andalas Faculty of Law Student Choir. The experimental group underwent 12 sessions of intensive training utilizing Solfège hand signs and culturally adapted rhythm syllables while musical proficiency was measured using a validated sight-singing test assessing pitch and rhythm accuracy. Quantitative analysis using an independent sample t-test revealed a statistically significant improvement in the experimental group (t=6.513, p0.05) with data distribution confirmed as normal (Kolmogorov-Smirnov 0.05). These findings demonstrate that the intervention successfully bridged the gap between aural imitation and theoretical understanding. Consequently, the study confirms that the Kodály Method is a highly effective and time-efficient pedagogical strategy for adult beginners. By fostering musical independence and self-correction, this approach reduces reliance on rote learning. The research recommends implementing these techniques in non-formal higher education vocal training to accelerate the transition from novice singer to independent musician.